2001
DOI: 10.1002/1097-0177(2000)9999:9999<::aid-dvdy1087>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of FGF and VEGF in angioblast induction and migration during vascular development

Abstract: The embryonic vasculature forms by the processes of vasculogenesis and angiogenesis. Angioblasts (endothelial cell precursors) appear to be induced by fibroblast growth factor 2 (FGF‐2). The angioblasts contributing to the dorsal aortae arise by an epithelial to mesenchymal transformation of cells originating from the splanchnic mesoderm. QH‐l and vascular endothelial growth factor receptor 2 (VEGFR‐2) both appear to label these cells as they adopt a mesenchymal morphology. Since VEGFR‐2 is the earliest known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(129 citation statements)
references
References 112 publications
(142 reference statements)
7
121
0
1
Order By: Relevance
“…In an attempt to explain why freshly isolated islets become more efficiently revascularised than cultured islets following transplantation, we measured concentrations of angiogenic factors in freshly isolated and cultured rat islets, as well as in 4-day-old and 1-month-old rat islet grafts. The process of angiogenesis has been extensively studied in different experimental setups, and the most important growth factors involved seem to be VEGF and bFGF [32][33][34]. Consistent with previous studies [35,36], we found that the islet production of VEGF increased markedly during culture.…”
Section: Discussionsupporting
confidence: 90%
“…In an attempt to explain why freshly isolated islets become more efficiently revascularised than cultured islets following transplantation, we measured concentrations of angiogenic factors in freshly isolated and cultured rat islets, as well as in 4-day-old and 1-month-old rat islet grafts. The process of angiogenesis has been extensively studied in different experimental setups, and the most important growth factors involved seem to be VEGF and bFGF [32][33][34]. Consistent with previous studies [35,36], we found that the islet production of VEGF increased markedly during culture.…”
Section: Discussionsupporting
confidence: 90%
“…Fibroblast growth factors (FGFs) play key roles in the induction of both angioblasts (Poole et al, 2001) and haemangioblasts (Poole et al, 2001;Cox and Poole, 2000) from the mesoderm, and most endothelial precursors divide and differentiate in response to vascular endothelial growth factor (VEGF) (Raffi, 2000;Isner and Asahara, 1999). Although the above is true in general, several studies have suggested that SMC-like cells can arise from atrio-ventricular and dorsal aorta ECs (Arciniegas et al, 1992;DeRuitar et al, 1997;Nakajima et al, 1997;Frid et al, 2002).…”
Section: Introductionsupporting
confidence: 84%
“…As stated above, the phenotype of fgfr knockout mice is scarcely informative even though adenovirus-drive dominant-negative FGFR1 expression leads to severe vascular alterations in mouse embryos [76]. Also, FGF2 promotes the proliferation and differentiation of VEGFR-2 + hemangioblast precursors from the mesoderm [114]. In embryoid bodies, embryonic stem cells can differentiate into a variety of cell lineages, including endothelial cells [115].…”
Section: Fgf/vegf Cross-talkmentioning
confidence: 99%